Case reportBlood vessel ultrastructural picture in a CADASIL patient diagnosed at an advanced age - Lewandowska, Eliza; Felczak, Paulina; Buczek, Julia; Gramza, Karolina; Rafałowska, Janina (Folia Neuropathologica, 2014)
We report the case of an 84-year-old male patient afflicted by cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL) showing minimal symptoms of disease. The patient was diagnosed on the basis of ultrastructural and genetic examinations. Ultrastructurally, a typical vascular pathology was found. However, in abnormal capillary vessel walls no granular osmiophilic material (GOM) was found. In the arteriole there were only a few GOM deposits that revealed various structures, of which only some resembled typical round GOM. The arteriolar walls showed severe damage, including fragmentation, degeneration and loss of vascular smooth muscle cells (VSMCs) with numerous deposits of elastin, mucosubstances, different granular debris, as well as collagen fibres in the basement membrane. Lysosomal inclusions with fingerprint morphology, atypical for CADASIL, were located in some of the VSMCs. Very old age at the onset of the disease may suggest that morphological changes in blood vessels, described in this report, may be due to both the disease and the patient’s age. To our best knowledge it is the first description of pathology of blood vessels and GOM morphology in a CADASIL patient diagnosed at an advanced age.